Pembelajaran Ips Dengan Menggunakan Model The Power Of Two Di Sekolah Dasar - Amin, Zakiyyul; Nasrul, Nasrul; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe and increase in student learning outcomes in social studies learning by using The Power Of Two model in the fifth grade of elementary school. Types of this research was classroom action research with qualitative and quantitative approach. The research subject was 28 grade V students. The research procedure consistend of planning, implementing, observing, and reflecting. The result of the study showed and increase in aspects: a) RPP cycle I with an average of 67,85% and cycle II 92,85%, b) implementation on the aspect of the teacher cycle I with an average of 70,53% and the second cycle 92,85%, the aspect of the students of the first cycle with an average 66,07% and cycle II 89,28%, c) learning outcomes in the first cycle with an average of 69,12% and cycle II 91,07%. The conclusions from the result of the research conducted are using the Make a Match model can improve student learning outcomes in social stundent learning in class V SD Negeri 11 Indarung Padang